1985
DOI: 10.1172/jci111907
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte membrane rigidity induced by glycophorin A-ligand interaction. Evidence for a ligand-induced association between glycophorin A and skeletal proteins.

Abstract: Erythrocyte skeletal proteins are known to play an important role in determining membrane deformability. In order to see whether transmembrane proteins also influence deformability and, if so, whether this influence is mediated by an interaction with the membrane skeleton, we examined the effect on deformability of ligands specific for transmembrane proteins. We found membrane deformability markedly reduced in erythrocytes that were pretreated with glycophorin A-specific ligands. In contrast, ligands specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
64
0
1

Year Published

1988
1988
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 39 publications
4
64
0
1
Order By: Relevance
“…43,44 It was concluded that the increase in membrane rigidity requires a ligand-induced interaction with GPA that subsequently alters the RBC cytoskeletal interactions. 44 Thus, MSP1 12 binding to GPA may also alter the RBC membrane properties during parasite invasion. Similarly, a separate study found that reduced RBC membrane deformability on GPA engagement correlated with reduced malaria parasite invasion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…43,44 It was concluded that the increase in membrane rigidity requires a ligand-induced interaction with GPA that subsequently alters the RBC cytoskeletal interactions. 44 Thus, MSP1 12 binding to GPA may also alter the RBC membrane properties during parasite invasion. Similarly, a separate study found that reduced RBC membrane deformability on GPA engagement correlated with reduced malaria parasite invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, antibodies targeting the trypsin-resistant region of GPA, a region that overlaps with the MSP1 12 binding site ( Figure 3A), caused a pronounced effect on RBC membrane rigidity. 43,44 It was concluded that the increase in membrane rigidity requires a ligand-induced interaction with GPA that subsequently alters the RBC cytoskeletal interactions. 44 Thus, MSP1 12 binding to GPA may also alter the RBC membrane properties during parasite invasion.…”
mentioning
confidence: 99%
“…42,43 The dynamic, energy-dependent link between cell membrane and skeleton is essential for the ability of RBCs to pass rapidly through capillaries. 44,45 Maintaining optimal RBC membrane deformability is thus critical for the body to insure appropriate perfusion of the tissues by preventing trapping of less deformable RBCs in capillaries. Therefore, we next investigated the effect of CR1 ligation on RBC membrane deformability by using 2 complementary methods: (1) LOT shape recovery and (2) filtration through microchannel networks.…”
Section: Discussionmentioning
confidence: 99%
“…21 Abnormal molecular interactions that result in cross-linking of cytoskeletal proteins can markedly increase the rigidity of RBCs, as evidenced by the reduced deformability of RBCs treated with monoclonal antibodies to glycophorin A that spans the RBC membrane and interacts with spectrin through protein 4.1. 22 Although the precise mechanisms leading to decreased deformability of PRBCs are poorly understood, the contribution of parasite proteins to increased membrane rigidity is most likely attributed to their direct or indirect interactions with proteins of the RBC membrane skeleton. KAHRP is known to associate with spectrin, actin, and ankyrin in the RBC skeleton 9,23,24 and may cross-link spectrin, resulting in increased membrane rigidity.…”
Section: Discussionmentioning
confidence: 99%